Keanekaragaman Serangga Fitofag pada Sengon Falcataria moluccana (Miq.) Barneby & J.W. Grimes dari Jawa dan Hawaii di Persemaian di Bogor - Yendra Pratama Setyawan; Purnama Hidayat; Hermanu Triwidodo; Kenneth Puliafico (Jurnal Ilmu Pertanian Indonesia, 2021)
Albizia (Falcataria moluccana) cultivated in Indonesia for timber plantations can increase the farmer’s income, even though albizia became an invasive alien species that can cause the economic and ecological losses. The controlling of invasive species using biological control is an effective method. The purpose of this study was to determine the phytophagous insects on albizia from Java and Hawaii in seedling in Bogor. The experiment was conducted in Carangpulang, Dramaga, Bogor. The experiment was arranged in a completely randomized block design using seed origin as a treatment (albizia Java and Hawaii) with 4 replicates. Total number of tree sample was 160 trees. Observations were conducted every 2 weeks until 32 weeks after planting. Identification of insects was conducted in the Laboratory of Insect Biosystematics, IPB. A total of 67 phytophagous insects were collected, 57 species in albizia from Java and 54 species in albizia from Hawaii. There was no difference in abundance and diversity of phytophagous insects on albizia from Java and Hawaii. Larvae of Eurema blanda (Lepidoptera: Pieridae) became an important pest causes leaf defoliation. Furthermore, Hulodes caranea (Lepidoptera: Noctuidae), Margarodes sp. (Hemiptera: Margarodidae), Choristoneura sp. (Lepidoptera: Tortricidae), and Adoxophyes sp. (Lepidoptera: Tortricidae) identified as important pests that have not been reported in the other research. Keywords: albizia, defoliator insect, Fabaceae, important pests, invasive alien species